The Degree of Familiarity With Kindergarten Teachers to Child Rights Principles Contained - A Field Study in Kindergartens Lattakia City - Mohamed, Mahmoud; Asaad, Shaza Abdulkareem (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The research aimed to recognize the degree of familiarity with kindergarten teachers to child rights principles contained from the manager’s and teachers’ point of view in Kindergartens Lattakia City, also tries to identify the differences in their opinions based on the following variables: ( job title, years of experience). The researcher used descriptive analytic method the study tool questionnaire consist of (52) paragraph. This tool was applicated on a sample of (178) managers and teachers during the 2017-2018. The results of the questionnaire were analyzed. To validate the tool, it was presented to a panel of seven (7) specialists. The instrument was validated by pilot administration to a random sample of (28) kindergarten managers and teachers, Cronbach’s Alpha equation that which reach (0.96), and (0.975) in Spearman Brown. The research results showed that the degree of familiarity with kindergarten teachers to child rights principles contained from the manager’s and teachers’ point of view in Kindergartens Lattakia City came of a medium degree, Also it was shown that there were differences of statistical indication between the sample research to the variable experience in favor of the higher experience, also to the variable job title in favor of the teachers. In the light of the results of the study the researcher recommends about: Need of more attention of the concerned authority to the provision of the Convention on the rights of the child, in all kindergartens. Work to held the lectures and seminars for the awareness of people, also conferences to be held concerning the rights of child covering all sides in regard to this field so as to protect childhood. Teaching the rights of child within the curriculum of the kindergarten sections in the faculties of education. Preparing courses for kindergarten teachers, to promote to the awareness on the child’s rights, and put the booklets and training manuals, which teachers the kindergarten to the best ways and means, to enable the child of it and satisfying him with it.